Aspek Pendidikan Demokrasi Pada Wayang Kampung Sebelah (Analisis Isi Lakon "Want to be Lurah" dengan Dalang Ki Jlitheng Suparman sebagai Media Pembelajaran Pendidikan Pancasila dan Kewarganegaraan) - Nugroho, Suryo Eko (2016)
This study aimed to describe the educational aspect of democracy in Wayang Kampung Next to The play Want to be Lurah as Instructional Media Pancasila and Citizenship Education. The research is a qualitative descriptive. This research is a case study of a single fixed. The subjects were Wayang Kampung Next to the play "Want to be Lurah" masterminded by Ki Dalang Jlitheng Supaman. The object of research is the educational aspect of democracy that is contained in Wayang Kampung Next to the play "Want to be Lurah" masterminded by Ki Dalang Jlitheng Supaman Source of the data contained in Wayang Kampung Next to the play "Want to be Lurah" is a scene or dialogue in which there are aspects of democracy education. Data collection techniques in this study are an interactive that includes technical documentation and study of literature. This study uses two kinds of triangulation is a triangulation of data sources and triangulation of data collection. The results of this study can be concluded that: 1) The educational aspect of democracy is pictured in the village next to the puppet play "Who Wants To Be Lurah". This is evidenced by the elections, chaired by the grandparent Sidik. Educational aspects of democracy are seen in the story of the puppet in accordance with the following indicators: 1) Accountability, 2) Rotation of power, 3) political Recruitment is open, 4) Election, and 5) The fulfillment of basic rights. The educational aspect of democracy contained in the Basic Competence Pancasila and Citizenship Education Class VIII, namely: Understanding the implementation of democracy in different aspects of life. The attitudes that describe aspects of democratic education is very important to be known and understood by every citizen so that no attempts abuse of power by those who are not responsible.